COMPLEX RECONSTRUCTION OF DEFECT OF THE LOWER THIRD OF THE NOSE - Santos, Guida; Goulão, João (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
Reconstruction of nasal defects must preserve the integrity of complex facial functions and expressions, as well as facial symmetry and a pleasing aesthetic outcome. The localization and size, the anatomical layers involved and the donor tissue availability must be considered in order to establish the indication of the proper surgical procedure. In any nasal reconstruction, it is necessary to take into account three layers: internal lining, cartilaginous framework and external covering. The authors describe the reconstruction of a full-thickness defect of the left lower third of the nose after excision of a recurrent basal cell carcinoma, with ipsilateral septal mucosal flap for reconstruction of the internal lining, free auricular cartilage graft for reconstruction of cartilaginous framework and nasolabial transposition flap for the external coating, in a unique surgical procedure and with acceptable functional and aesthetic final results.